High-Frequency Ultrasound for the Study of Early Mouse Embryonic Cardiovascular System. (December 2015) - Greco, Adelaide; Coda, Anna Rita Daniela; Albanese, Sandra; Ragucci, Monica; Liuzzi, Raffaele; Auletta, Luigi; Gargiulo, Sara; Lamagna, Francesco; Salvatore, Marco; Mancini, Marcello
An accurate diagnosis of congenital heart defects during fetal development is critical for interventional planning. Mice can be used to generate animal models with heart defects, and high-frequency ultrasound (HFUS) imaging enables in utero imaging of live mouse embryos. A wide range of physiological measurements is possible using Doppler-HFUS imaging; limitations of any single measurement warrant a multiparameter approach to characterize cardiovascular function. Doppler-HFUS was used to explore the embryonic (heart, aorta) and extraembryonic (umbilical blood flow) circulatory systems to create a database in normal mouse embryos between 9.5 and 16.5 days of gestation. Multivariate analyses were performed to explore correlations between gestational age and embryo echocardiographic parameters. Heart rate and peak velocity in the aorta were positively correlated with gestational time, whereas cardiac cycle length, isovolumetric relaxation time, myocardial performance index, and arterial deceleration time of the umbilical cord were negatively correlated with it. Doppler-HFUS facilitated detailed characterization of the embryonic mouse circulation and represents a useful tool for investigation of the early mouse embryonic cardiovascular system.